KASTAMONU-TAŞKÖPRÜ ORMAN FİDANLIĞINDA ÜRETİLEN 2+0 YAŞLI SARIÇAM (Pinus sylvestris L.) FİDANLARININ TSE NORMLARINA GÖRE DEĞERLENDİRİLMESİ - Ayan, Sezgin; Demircioğlu, Nurcan; Avanoğlu, Birsel; Sıvacıoğlu, Ahmet (YTÜ, SİGMA, Mühendislik ve Fen Bilimleri Dergisi, 2, 73–83, İstanbul., 2005)
Bu çalışmada, Kastamonu-Taşköprü Orman Fidanlığında üretilen 2+0 yaşlı çıplak köklü sarıçam fidanları kullanılmıştır. Daday-Koldandere orijinli fidanların morfolojik karakterleri belirlenerek, TS 2265/Şubat 1988 kalite sınıflamasına uygunluğu irdelenmiştir. Ayrıca, söz konusu sarıçam fidanlarının hem TSE ve hem de yeni oluşturulan kalite sınıflamasının hassasiyeti diskriminant analizleri ile denetlenmiştir. Çalışma sonucunda; üretilen 2+0 yaşlı sarıçam fidanlarının boyu 11.62 cm, kök boğazı çapı 2.93 mm, gürbüzlük indisi 40.14, katlılık 2.34, kuru kök % 30.65, kalite indeksinin 0.32 ortalama değerlerde olduğu tespit edilmiştir. TS kalite sınıflamasına göre; deneme materyali olarak kullanılan fidanların fidan boyu bakımından %92.7’si, kök boğazı çapı bakımından %98.7’si, fidan boyu-kök boğazı çapı bakımından %91.4’ü, katlılık kriteri bakımından %92,7’si I. kalite sınıfında yer almaktadır. In this study; 2+0 aged, bare root, Daday-Koldandere origin of Scotch pine seedlings, produced at Kastamonu–Taskopru forest nursery, were used. First the morphological characters of the seedlings were determined and the appropriateness to TS 2265/February 1988 were examined. Furthermore, the sensitiveness of quality classification both TSI and newly formed for the mentioned scotch pine seedlings were checked with discriminate analysis. In the conclusion, the average values of the seedling height, the root collar diameter, seedling height / root collar diameter ratio, stem dry weight / root dry weight ratio, dry root percent, quality index of 2+0 aged scotch pine seedlings were determined as 11.62 cm, 2.93 mm, 40.14, 2.34, 30.65 %, 0.32 respectively. In addition, 92.7 % of the seedlings as to the seedling height criterion, 98.7 % of the seedlings as to the root collar diameter criterion, 91.4 % of the seedlings as to the seedling height - root collar diameter criterion, 92.7 % of the seedlings as to the stem dry weight / root dry weight ratio criterion were included in first quality class in respect of TSI quality classification
EVALUATION OF 2+0 AGED NURSERY OF THE SCOTCH PINE (Pinus sylvestris L.) RAISED IN KASTAMONU-TASKOPRU FOREST NURSERY AS TO TSI QUALITY CLASSIFICATION
Keywords: Sarıçam, TSE, Fidan, Kalite, Taşköprü; Scotch Pine, TSI (Turkish Standards Institute), Seedling, Quality, Taşköprü.